ANALISIS YURIDIS ATAS TURUNNYA KEKUATAN PEMBUKTIAN AKTA NOTARIS MENURUT UUJN NO. 2 TAHUN 2014 TENTANG JABATAN NOTARIS - FELIX CHRISTIAN ADRIANO (PREMISE LAW JURNAL, 2015)
The result of the research showed that the lower level of the force of evidence of Notarial deeds was based on Article 16, paragraph 1, paragraph 7, and paragraph 8, Article 41 with reference to Article 38, Article 39, Article 40, Article 44, Article 48, Article 50, and article 52 of Notarial Act No. 2/2014. Violating these Articles will cause an authentic deed to be lower so thast it turned to an underhanded deed. These articles do not legally protect the position of a Notary because they are not needed through a judge’s verdict to prove the force of evidence of a Notarial deed. Verification for a Notarial deed which has the force of evidence as an underhanded deed must be done through a claim to a District Court to prove whether it violates the Articles above or not. If a Notary violates the provision under the Articles above, through the court’s verdict, he will be given a written warning, suspension, honorable discharge, and dishonorable discharge; according to the civil law, he has to reimburse the cost, the compensation, and interest. Keywords: The Force of Evidence of Notarial Deed